+0  
 
+5
68
1
avatar

My solution was: -.3, which is wrong...

The right solution should be: 1.3

 

I followed these steps:

 

2*(1/3)^(0.3-x)-4=2

2*(1/3)^(0.3-x)=-2

(1/3)^(0.3-x)=-1

(1/3)^(0.3-x)=-(1/3)^0

0.3-x=0

x=.3

Guest Feb 14, 2017
edited by Guest  Feb 14, 2017
edited by Guest  Feb 14, 2017
Sort: 

1+0 Answers

 #1
avatar+75333 
0

2*(1/3)^(0.3-x)-4=2  add 4 to both sides

 

2*(1/3)^(0.3-x) = 6     divide both sides by 2

 

(1/3)^(.3 - x)  = 3      

 

Note......  (1/3)^(.3 - x)  = 1 / [ 3^(.3 - x)] =   3^[ - ( .3 - x)]   = 3^(x - .3)

 

3^(x - .3)  = 3^1        equate exponents

 

x - .3  = 1     add .3 to both sides

 

x  = 1.3

 

 

cool cool cool

CPhill  Feb 14, 2017

13 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details